Determinants of Liquidity, Profitability, Debt Policy, and Dividend Policy towards The Recovery of Sharia Stock Company Value - Silaen, Musa Fernando; Supitriyani, Supitriyani (Asosiasi Dosen Akuntansi Indonesia, 2022)
The purpose of this study is to find out the picture of liquidity, profitability, debt policy, dividend policy and company value, as well as to determine the determination between liquidity, profitability, debt policy, dividend policy in recovering company value both simultaneously and partially. This research uses qualitative descriptive analysis methods as well as quantitative descriptive analysis. Hypothesis test with simultaneous test (Test F), the results were obtained that liquidity, profitability, debt policy and dividend policy have a significant effect on the company's value in the Jakarta Islamic Index Company. Hypothesis test with partial test (Test t), it was obtained that liquidity and debt policy have an insignificant effect on company value, while profitability and dividend policy have an effect and significantly affect the company's value on the Jakarta Islamic Index. Companies should be able to pay attention to the company's ability to generate profits and optimize the use of external financing (debt management) and the company should be more optimal in distributing profits to shareholders or saving profits owned to invest them in the future. In addition, companies should also better understand business conditions such as the company's strengths and opportunities to make a profit and be able to increase the value of the company in the future.